2014
DOI: 10.3892/mco.2014.475
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of CyberKnife for inoperable stage I peripheral non-small-cell lung cancer compared to three-dimensional conformal radiotherapy

Abstract: Abstract. This study was conducted to compare the clinical curative effect and acute radiation lung reactions between CyberKnife (CK) and three-dimensional conformal radiotherapy (3DCRT) treatment for inoperable stage I peripheral non-small-cell lung cancer (NSCLC). We retrospectively analyzed 68 patients with inoperable stage I peripheral NSCLC between 2012 and 2013 in our institution. The CK patients were treated with 42-60 Gy in three fractions, while the 3DCRT patients were treated with a total of 60 Gy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…intervention and comparison: SBRT versus CRT (including conventional radiotherapy, [ 15 , 16 , 19 , 21 , 26 ] conventional fractionated radiotherapy, [ 17 , 20 , 23 , 25 , 27 ] 3D conformal radiotherapy, [ 9 , 11 , 13 , 14 , 18 ] and accelerated hypofractionated radiotherapy [ 13 ] );…”
Section: Methodsmentioning
confidence: 99%
“…intervention and comparison: SBRT versus CRT (including conventional radiotherapy, [ 15 , 16 , 19 , 21 , 26 ] conventional fractionated radiotherapy, [ 17 , 20 , 23 , 25 , 27 ] 3D conformal radiotherapy, [ 9 , 11 , 13 , 14 , 18 ] and accelerated hypofractionated radiotherapy [ 13 ] );…”
Section: Methodsmentioning
confidence: 99%
“…Cyberknife ® stereotactic radiation therapy for stage I lung cancer and pulmonary metastases: evaluation of local control at 24 months movement, loco-regional control and survival have proven to be disappointing with conventional radiation therapy even if the SPACE phase II randomized study showed encouraging results for high precision 3D radiotherapy. This is probably due to a reduced biological dose-effect and a lower conformity index (1).…”
Section: Original Articlementioning
confidence: 99%
“…Prior studies of CyberKnife ® have reported local control rates of 90-97% at 2-3 years of follow-up, with low toxicities (1,(5)(6)(7). Treatment with CyberKnife ® can also allow for a sustainable local control rate of 89% with a median follow-up of 12 months in oligometastatic lesions, with few morbidities (8).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary injuries are limiting factors for the use of radiotherapy for the treatment of thoracic cancers [1,2,3,4,5,6]. Clinically significant lung injury has been estimated to occur in ~10%–30% of patients undergoing radiotherapy for cancers in the thoracic region [7,8], and pulmonary effects have also been observed in patients undergoing radiotherapy for cancer treatment or bone marrow transplantation [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%